Fiscal policy and the natural resources curse how to escape from the poverty trap - Mosley, Paul (Routledge studies in development economics, 2017)
It is widely accepted that natural resource wealth, especially in the form of oil and minerals, can be a key factor in inhibiting economic development. Many of the countries that are richest in natural resources – including oil, metals and diamonds – are amongst the world’s poorest. Why?